Management Analysis of The Suaman Hot Springs Tourist Attraction Pawan Village, Rokan Hulu Regency, Riau - Asyim, Fauzan; Eka Asih Febriani; Rahmad Hidayat (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study aims to determine the analysis of the management of the suaman hot springs tourism object in pawan village, rambah district, rokan hulu regency. research indicators include tourism facilities, tourism management, tourism quality and tourism impact. this can be seen from the suaman hot springs tourism object which has received less attention from the local government and also there are still many people who do not maintain this tourist attraction properly, it can be seen from the facilities at the suaman hot springs tourist attraction which are still poorly maintained and managed. so that many visitors who come to the suaman hot springs tourist attraction but cannot enjoy the facilities provided and the lack of participation of the local community and visitors in maintaining existing facilities. this study uses qualitative research methods, data collection techniques namely observation, interviews and documentation. the results in this study the management of the suaman hot springs tourism object is currently still carried out locally by the village community with a lack of involvement from the local government. this has an impact on the lack of coordination in planning, implementation, and supervision of tourism activities so that tourism supporting facilities and infrastructure are still inadequate.